2021
DOI: 10.3390/polym13111847
|View full text |Cite
|
Sign up to set email alerts
|

Wear Assessment of Tibial Inserts Made of Highly Cross-Linked Polyethylene Supplemented with Dodecyl Gallate in the Total Knee Arthroplasty

Abstract: Background: the wear of tibial insert is still one of primary factors leading to failure of total knee arthroplasty (TKA). Dodecyl gallate (DG) has shown improvements in the oxidation stability of highly cross-linked polyethylene (HXLPE). This study aimed to assess the application of HXLPE supplemented with DG (HXLPE-DG) on the tibial insert in TKA concerning the wear resistance and the potential impact on implant fixation; Methods: tibial inserts made of HXLPE-DG were subjected to a 3 million loading-cycle we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…A previous study from our research group reported that unaged HXLPE-DG knee inserts had a wear rate of 3.92 mg/million cycles [ 1 ], which was similar to the results of this study, although the earlier study did not consider the aged specimen. Haider et al reported UHMWPE tibial inserts with a wear rate of 19.88 mg/million cycles [ 15 ], which was more than four times that of HXLPE-DG.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study from our research group reported that unaged HXLPE-DG knee inserts had a wear rate of 3.92 mg/million cycles [ 1 ], which was similar to the results of this study, although the earlier study did not consider the aged specimen. Haider et al reported UHMWPE tibial inserts with a wear rate of 19.88 mg/million cycles [ 15 ], which was more than four times that of HXLPE-DG.…”
Section: Discussionsupporting
confidence: 88%
“…The reason may be that the cross-linking process reduces the deformability of the polyethylene inserts, resulting in less fibrous particles [ 31 , 32 ], and larger polyethylene particles could be crushed under the action of cyclic stress. At the same time, the proportion of large strip-shaped, needle-shaped, and fibrous particles was greatly reduced [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that a neutral alignment did not improve the clinical outcome or survival rate, and a tolerance of 3° varus to 3° valgus could not be considered a “safe zone” with modern personalized alignment strategies, especially for an updated prosthesis ( Tibbo et al, 2021 ; Schelker et al, 2022 ). A possible reason is considerable differences in the design of contemporary knee prostheses, which can affect the mechanical behavior and wear performance ( Asseln et al, 2021 ; Zhang et al, 2021 ; Su et al, 2022 ). Although advanced techniques, like personalized specific instrumentation, navigation systems, and robotic surgeries, have improved surgical precision and alignment accuracy, malalignment is still a common complication.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee replacement (henceforth TKR) is successfully utilized to treat severely degenerated joints and is a standard procedure for treating osteoarthritic discomfort. A conventional TKR implant consists of a metallic femoral and a tibial element embedded into the femur and the tibia bone, respectively, and an insert (referred to as spacers) made of ultra-high molecular weight polyethylene (henceforth UHMWPE) (2) . Wear is a persistent problem in TKR because of its inconsistent and occasionally unstable form (2) , which may eventually cause aseptic loosening, osteolysis, periprosthetic issues (3) and premature failure (2,3) .…”
Section: Introductionmentioning
confidence: 99%